Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IV Materi Bangun Datar Segi Empat SD Negeri 19 Ujuang Guguak - Afdanil Adha; Fauzi Fadliansyah (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
In mathematics lessons that discuss geometry, students still appear confused when asked to name the sides of a square and differentiate between the length and width of a rectangle. This research aims to apply the problem based learning model to flat shape material in class IV of SD Negeri 19 Ujuang Guguak on geometry material. The results of the research show that the problem based learning model can improve student learning outcomes at SDN 19 Ujuang Guguak. Before action was taken, the number of students who completed was only 3 people with a completion percentage of 15%. In cycle I the number of students who completed increased to 6 people with a completion percentage of 30%. In cycle II the number of students who completed increased to 17 people and the percentage of completion increased to 85%.